2007
DOI: 10.1103/physrevb.75.214112
|View full text |Cite
|
Sign up to set email alerts
|

Compressive stress effects on nanoparticle modulus and fracture

Abstract: Individual nanoparticles of silicon and titanium having diameters in the range of 40-140 nm have been repeatedly compressed by a nanoindenter. Even at low loads, the small tip-particle and particle-substrate contacts generate extreme pressures within the confined particle, influencing its stiffness and fracture toughness. The effect of these high pressures on the measured modulus is taken into account by invoking a Murnaghan equation-of-state-based analysis. Fracture toughness of the silicon particles is found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 26 publications
(25 reference statements)
2
84
0
Order By: Relevance
“…79 In situ TEM compressive experiments on the Si NWs and particles have also been conducted. [80][81][82] Highly ductile features, plastic dislocations and strong strain hardening were directly observed. These results apparently indicated that for the semiconducting or ceramic materials, the RT brittle-ductile transition can be realized by reducing the size of the materials.…”
Section: Direct Atomic Mechanisms Of the Size Effect On The Unusual Pmentioning
confidence: 97%
“…79 In situ TEM compressive experiments on the Si NWs and particles have also been conducted. [80][81][82] Highly ductile features, plastic dislocations and strong strain hardening were directly observed. These results apparently indicated that for the semiconducting or ceramic materials, the RT brittle-ductile transition can be realized by reducing the size of the materials.…”
Section: Direct Atomic Mechanisms Of the Size Effect On The Unusual Pmentioning
confidence: 97%
“…[13][14][15] Nevertheless, there have been fewer studies dealing with the fracture properties of relatively brittle, stand-alone, small volumes. While there have been a few semi-quantitative studies of nanospheres, [16] nanowires, [17] and nanopillars, [18] there has been no coupled, property measurements Robust nanostructures for future devices will depend increasingly on their reliability. While great strides have been achieved for precisely evaluating electronic, magnetic, photonic, elasticity and strength properties, the same levels for fracture resistance have been lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[131][132][133] Both of them influence elastic moduli variations: the smaller the system, the more the effective moduli differ from their bulk counterpart. Atomistic simulations show significant variations of the effective elastic moduli below 10-15 nm sized NPs only, 134 while changes are still observed at rather greater sizes in the experiments (see, for example, Mook et al 135 ). Many differences between the two approaches need to be explained, and there is still no method to predict the evolution of elastic moduli due to size diminution for a given material (see Gerard and Pizzagalli for quantitative examples 136 ).…”
Section: Mechanics Of Nanoparticles: a Perspective Crossing Atomismentioning
confidence: 99%